Low serum 1, 25(OH)2D3 in end-stage renal disease: is reduced 1α-hydroxylase the only problem?. Issue 10 (11th October 2021) - Huish, Sharon A; Jenkinson, Carl; Dunn, Janet A; Meredith, David J; Bland, Rosemary; Hewison, Martin
Abstract : Low serum 1, 25-dihydroxyvitamin D (1, 25(OH)2 D) in end-stage renal disease (ESRD) is considered a consequence of elevated fibroblast growth factor 23 (FGF23) and concomitant reduced activity of renal 1α-hydroxylase ( CYP27B1 ). Current ESRD treatment strategies to increase serum calcium and suppress secondary hyperparathyroidism involve supplementation with vitamin D analogues that circumvent 1α-hydroxylase. This overlooks the potential importance of 25-hydroxyvitamin D (25(OH)D) deficiency as a contributor to low serum 1, 25(OH)2 D. We investigated the effects of vitamin D (cholecalciferol) supplementation (40, 000 IU for 12 weeks and maintenance dose of 20, 000 IU fortnightly), on multiple serum vitamin D metabolites (25(OH)D, 1, 25(OH)2 D3 and 24, 25(OH)2 D3 ) in 55 haemodialysis patients. Baseline and 12 month data were compared using related-samples Wilcoxon signed rank test. All patients remained on active vitamin D analogues as part of routine ESRD care. 1, 25(OH)2 D3 levels were low at baseline (normal range: 60–120 pmol/L). Cholecalciferol supplementation normalised both serum 25(OH)D and 1, 25(OH)2 D3 . Median serum 25(OH)D increased from 35.1 nmol/L (IQR: 23.0–47.5 nmol/L) to 119.9 nmol/L (IQR: 99.5–143.3 nmol/L) ( P < 0.001). Median serum 1, 25(OH)2 D3 and 24, 25(OH)2 D3 increased from 48.3 pmol/L (IQR: 35.9–57.9 pmol/L) and 3.8 nmol/L (IQR: 2.3–6.0 nmol/L) to 96.2 pmol/L (IQR: 77.1–130.6 pmol/L) and 12.3 nmol/L (IQR: 9–16.4 nmol/L), respectively ( P < 0.001). A non-significant reduction in daily active vitamin D analogue dose occurred, 0.94 µmcg at baseline to 0.77 µmcg at 12 months ( P = 0.73). The ability to synthesise 1, 25(OH)2 D3 in ESRD is maintained but is substrate dependent, and serum 25(OH)D was a limiting factor at baseline. Therefore, 1, 25(OH)2 D3 deficiency in ESRD is partly a consequence of 25(OH)D deficiency, rather than solely due to reduced 1α-hydroxylase activity as suggested by current treatment strategies.